GASTROINTESTINAL SYMPTOMS ARE ASSOCIATED WITH SEVERITY OF CORONAVIRUS DISEASE 2019: A SYSTEMATIC REVIEW - Ardena Lianto, Lie Milka (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Aim: This study aims to summarize and evaluate the association between GI symptoms in COVID-19 and disease severity. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded. Results: Database searches identified a total of 17632 articles. Of these, 100 articles passed the screening process, resulting in 15 articles for full-text assessment. Among them, 6 articles did not evaluate the outcome of interest. Hence, we found 9 appropriate studies included. Conclusion: Current findings are insufficient to establish a association between GI symptoms and disease severity in COVID-19 patients.